Determination of the sequence of intersecting lines using Focused Ion Beam/Scanning Electron Microscope - Kim, Jiye; Kim, MinJung; An, JinWook; Kim, Yunje (WILEY-BLACKWELL, 2016)
The aim of this study was to verify that the combination of focused ion beam (FIB) and scanning electron microscope/energydispersive X-ray (SEM/EDX) could be applied to determine the sequence of line crossings. The samples were transferred into FIB/SEM for FIB milling and an imaging operation. EDX was able to explore the chemical components and the corresponding elemental distribution in the intersection. The technique was successful in determining the sequence of heterogeneous line intersections produced using gel pens and red sealing ink with highest success rate (100% correctness). These observations show that the FIB/SEM was the appropriate instrument for an overall examination of document.